A kissúlyúság oka a várandós anya helytelen életmódja? - Molnár, Attila (Szociológiai Szemle, 2024)
The paper analyses the causes of the evolution of small weight and partly some of its consequences. It attempts to explore those endangering factors which may lead to an irregular outcome of pregnancy. It wishes to call attention to the greatness of the expectant mother’s responsibility by the calculation and presentation of the ratio of chance belonging to the individual endangering factors based on a sample. Though the most important person is the expectant mother herself, the influence of her close environment - such as the family - and the broader society, including the place of work, cannot be disregarded either.During the course of the study which is the basis of the paprs, 6848 mothers were questioned right after giving birth and we have reached the results published in the paper after the analysis of their answers.According to our experience the most harmful endangering factor is the active and passive smoking of expectant mothers and their heavy physical work. How a person’s conditions of work would change and how he or she shapes his or her life, primarily depends on school education, but marital ststus has a decisive role in the case of women.